Carbon-nanotube-based devices for passively mode-locked fiber laser applications - Liu, Huanhuan (2014)
Passively mode-locked fiber lasers generating ultrashort pulses have emerged as one of the best light sources in a range of applications including optical communication, frequency metrology, microscopy, and micromachining. One of the key components in passively mode-locked fiber lasers is saturable absorber (SA), which functions to reshape and stabilize intra-cavity pulses through nonlinear absorption. Semiconducting carbon nanotubes (CNTs) have been found to have nonlinear absorption properties in the near-infrared region, and explored extensively as SAs in mode-locked fiber lasers. Such carbon-nanotube-based saturable absorbers (CNT-SAs) could assist mode-locked fiber lasers to produce pulses with excellent performance in both time domain and frequency domain. However, there are still a lot of challenges regarding implementation of CNT-SAs in passively mode-locked fiber lasers such as the relatively low thermal damage threshold of CNT-SAs that limits the intra-cavity power, and the non-optimization modulation depth of CNT-SAs that leads to the unstable pulses in dispersion-managed mode-locked fiber lasers with near-zero net cavity dispersion.This thesis focuses on the investigation of CNT-based devices and their performance analysis of passively mode-locked fiber laser applications. Different methodologies of CNT deposition to obtain good performance CNT-SAs have been investigated. They include spray-coating, optically-driven deposition, chemical vapor deposition (CVD) of random or aligned CNTs. The main achievements in terms of passively mode-locked fiber laser applications utilizing the fabricated CNT-SAs are summarized as follows.In order to enhance the thermal damage threshold of CNT-SAs, a novel scheme of fiber-end-type CNT-SA has been proposed. The CNT-layer is optically deposited on fiber connector ends in a ring pattern for evanescent-field interaction rather than direct interaction. By controlling the inner ring diameter of the deposited CNT-layer, the fiber-end-type CNT-SAs can endure various levels of incident optical power. Experimental results show that the thermal damage threshold of CNT-SA with the inner ring diameter of ~10 μm can be enhanced by ~130% compared to the one without ring pattern. By incorporating the prepared CNT-SAs into an all-fiber Fabry-Perot (FP) laser, the laser can produce pulses with high pulse energy of ~114 nJ in the Q-switching regime, and pulses with short pulse width of ~680 fs as well as high repetition rate of ~211.84 MHz in the mode-locking regime.The next part focuses on stable pulse generation from dispersion-managed mode-locked fiber lasers with near-zero net cavity dispersion. We figure out that the optimization of modulation depth of SAs is necessary based on the experimental and numerical investigations. Experimental results show that there is an unstable region in the mode-locked fiber lasers with near-zero net cavity dispersion where the lasers only produce random pulse bursts rather than stable pulse trains. Through the implementation of the fabricated high-contrast CNT-SAs in the mode-locked fiber laser, such unstable region can be shrunk by ~31.3% when the modulation depth of CNT-SAs increases from 6.4% to 12.5%. Numerical simulation is found to be consistent with experimental observation. The obtained results are not only applicable to dispersion-managed mode-locked fiber lasers incorporating CNT-SAs, but also provide a general guidance for lasers using similar type of SAs. The CNT-SA incorporated dispersion-managed fiber laser with near-zero net cavity dispersion has been further applied in fiber-based supercontinuum (SC) generation. Pulse trains with low timing jitter of ~35 fs and pulse width of ~620 fs have been produced from the dispersion-managed mode-locked fiber laser and launched into a piece of normal-dispersion highly-nonlinear photonic crystal fiber (PCF). The SC output from the PCF covers 223 nm with less than 7-dB power fluctuation showing potential applications in optical communication and frequency metrology.